Are Over-the-Counter Hearing Aids Affordable, Accessible, and Satisfactory? Insights from MarkeTrak 25 Survey Data - Picou, Erin M.; Huang, Haiping (Seminars in Hearing, 2025)
The purpose of this study is to review the current state of the over-the-counter (OTC) hearing aid market, specifically focusing on adoption, affordability, accessibility, and satisfaction rates in the MarkeTrak 2025 survey. In a large-scale consumer survey, nearly 5,000 adults with perceived hearing difficulties completed a survey, which asked questions about, among other things, their hearing aids. The results of the survey suggest OTC hearing aids have had a small incremental increase (4 percentage points) in hearing device adoptions, a smaller impact than earbuds with features designed to support hearing loss. The introduction of OTC hearing aids has not affected the adoption rates of prescription hearing aids, where adoption rates (currently 39%) have been stable, or even increased, over the last decade. The data also demonstrate that most OTC hearing aid owners received some professional services, suggesting the accessibility of OTC hearing aids might not be fully successful if success means the ability to acquire hearing aids without professional support. However, OTC hearing aids have been successful in other respects. Relative to prescription hearing aids, OTC hearing aids are more affordable and have similarly high satisfaction rates. The OTC and earbud devices will be interesting to continue to monitor as the market adjusts to the widespread availability of direct-to-consumer solutions for management of hearing difficulties in adults. To date, the availability of OTC hearing aids has not disrupted the prescription hearing aid market, although they are more affordable, and most people who use them are satisfied.
Keywords: hearing aid; OTC; affordability; accessibility; satisfaction